The Undiscovered Self : With Symbols and the Interpretation of Dreams (New in Paper). - Jung, C. G. (Jung Extracts Ser., 2012)
These two essays, written late in Jung's life, reflect his responses to the shattering experience of World War II and the dawn of mass society. Among his most influential works, "The Undiscovered Self" is a plea for his generation--and those to come--to continue the individual work of self-discovery and not abandon needed psychological reflection for the easy ephemera of mass culture. Only individual awareness of both the conscious and unconscious aspects of the human psyche, Jung tells us, will allow the great work of human culture to continue and thrive. Jung's reflections on self-knowledge.